2006
DOI: 10.1300/j366v05n02_07
|View full text |Cite
|
Sign up to set email alerts
|

The Climate for Service

Abstract: We develop a framework in which internal employees' diagnoses of their firm's service climate determine their role behavior towards customers and, ultimately, customer satisfaction, loyalty, retention and shareholder value. Elements of the framework include: (1) foun-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Citing the work of Wiley (1991), Tornow and Wiley (1991), and Ulrich, Halbrook, Meder, Stuchlik, and Thorpe (1991), Schneider, Bowen, Ehrhart and Holcombe (2000) state that ‘job satisfaction and commitment surveys when aggregated to the unit level (…) reveal significant relationships with customer satisfaction …’ (p. 32). Furthermore, both Ryan et al (1996) and Koys (2001) have reported correlations between customer satisfaction and measures of employee satisfaction.…”
Section: The Service Profit Chainmentioning
confidence: 99%
“…Citing the work of Wiley (1991), Tornow and Wiley (1991), and Ulrich, Halbrook, Meder, Stuchlik, and Thorpe (1991), Schneider, Bowen, Ehrhart and Holcombe (2000) state that ‘job satisfaction and commitment surveys when aggregated to the unit level (…) reveal significant relationships with customer satisfaction …’ (p. 32). Furthermore, both Ryan et al (1996) and Koys (2001) have reported correlations between customer satisfaction and measures of employee satisfaction.…”
Section: The Service Profit Chainmentioning
confidence: 99%
“…For example, a more positive organizational climate likely leads to better communication among employees, greater cooperation and collaboration, greater mutual trust and understanding, and more active engagement of employees in group tasks—which will more than likely result in greater organizational performance. Indeed, many studies have shown stronger relations between positive perceptions of the job/workplace and organizational performance than between positive perceptions of the job/workplace and individual performance (Koys, 2001; Ostroff, 1992; Ryan, Schmit, & Johnson, 1996; Schneider, 1990; Schneider & Bowen, 1985; Schneider, White, & Paul, 1998). These results lead us to expect organizational climate to relate more strongly to employee job satisfaction, performance, and turnover when examined at the organizational level.…”
Section: Approaches To What Grouped Data Representmentioning
confidence: 99%
“…Findings of past studies in the context of the Kopelman et al model lead to several hypotheses regarding relations among organizational climate and performance, and employee job satisfaction and turnover. Employees who have positive perceptions of organizational climate are likely to work harder and, in turn, the organization is likely to be more productive and profitable than organizations in which employees have negative perceptions of organizational climate (Koys, 2001; Ostroff, 1992; Ryan et al, 1996; Schneider, 1990; Schneider & Bowen, 1985; Schneider et al, 1998). Conditions of the workplace, in particular, administrative support and employee participation in developing organizational policies and procedures, have been also associated with employee satisfaction and commitment to the organization (see Ingersoll, 2001, p. 506).…”
Section: Study Hypothesesmentioning
confidence: 99%
“…Aggregation is also common in organizational research. Thus, Schneider, Bowen, Ehrhart, and Holcombe (2000) could cite a body of research showing that "job satisfaction and commitment surveys when aggregated to the unit level . .…”
Section: Levels Of Analysis and Aggregationmentioning
confidence: 99%